The Effect of Digital Marketing Dimensions on Brand Awareness and Purchase Decisions through Brand Awareness in MSMEs - Mohammad Aldrin Akbar (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study aims to examine the influence of digital marketing dimensions, such as social media marketing, content marketing, email marketing, and online advertising, on purchase decisions, while also analyzing the mediating role of brand awareness in the context of the MSMEs digital economy. A quantitative approach using PLS-SEM with 5,000 bootstrap resamples was applied to analyze direct and indirect relationships among variables based on data from MSME consumers. The findings reveal that social media marketing has the strongest direct effect on purchase decisions and also significantly enhances brand awareness. Content marketing and online advertising significantly improve brand awareness but do not directly influence purchase decisions. Instead, their effects on purchasing behavior occur indirectly through brand awareness. Email marketing shows no significant impact on either brand awareness or purchase decisions. Furthermore, brand awareness significantly affects purchase decisions and mediates the effects of content marketing, online advertising, and social media marketing, but not email marketing. These results highlight the central role of brand awareness as a cognitive bridge between digital marketing strategies and consumer behavior. For MSMEs, engagement-driven and awareness-building strategies are more effective than direct promotional communication in driving purchasing decisions.